Descriptive Analysis of Cases with Suspected Infections that Used 16S Ribosomal RNA PCR Testing. (4th October 2017) - Munoz, Francisco Hernandez; Paez, Armando; Visintainer, Paul; Lindsey, Kristy; Moore, Franklin
Abstract: Background: Culture-based bacterial identification is important in the management of infections, but can be a laborious effort and can be limited by prior antibiotic (abx) use. There is limited data on the clinical value and effective implementation of 16s ribosomal RNA PCR (16s). The objective is to describe cases in which 16s was used in suspected infections. Methods: Descriptive analysis of all culture-negative cases of suspected infections in a large tertiary hospital where 16s was utilized from January 1, 2014 to Jul 13, 2016, was performed as part of an IRB-approved study. Test was performed by an outside laboratory when requested by an ID specialist, and bacterial cultures were negative (-) for at least 72 hours in sterile body fluid or tissue specimens. Results: 16s was used in 70 cases: 24/70 (34.3%) were positive (+) with 20 (83.3%) having received prior antibiotics. At least 1change in abx plan was made in 17 (70.8%) cases: 14 changed to narrower spectrum and 6 in duration. Among (−) 16s, 14/36 (30.4%) had at least 1change in abx plan (8/14 stopping abx, 4/14 to narrower spectrum). Fever (> T 100.3F) within 24 hours of admission was more common in (+) vs. (-) 16s (9/24 vs. 3/46, P = 0.01). Number of abx changes was higher in (+) than (-) 16s (1.6 ± 1.2 [SD] vs. 0.8 ± 0.9 [SD], P = 0.004). Rate of empiric non-targeted antibiotic use after ID consult, was not different in (+) vs (−)16s (0.6 ± 0.4 vs. 0.7 ± 0.4, P = 0.34). Hospital stay was longer with (+) vs (−) 16s (12.7 ± 7.4 [SD] vs. 8.4 ± 5.3 [SD] days, P = 0.007).This was probably affected by the underlying diagnoses and illness severity. Mean turnaround time for results was 10.8 days (3–25, range). Yield of test was high in empyema (80%). Many of the isolated organisms were Streptococcus sp. and anaerobes. Conclusion: 16s in culture-negative specimens can lead to specific microbiologic diagnosis in 34% of cases despite 80% receiving antibiotics prior to sampling. Changes in abx plan occurred in 44% of all cases. Within (-) 16s results, 30.4% had a change in abx plan, 17.4% having discontinued abx. Streptococcus sp. and anaerobes were the commonly isolated organisms and with highest test yield in empyema.16s has clinical utility that may be even greater if the turnaround time is shortened. Disclosures: All authors: No reported disclosures.